2017
DOI: 10.1080/22201181.2017.1401773
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the labour epidural rate in a state hospital in South Africa: challenges and opportunities

Abstract: Background: A 2012 audit on labour epidural analgesia rates in Tygerberg Hospital (TBH) revealed that only 2.2% of labouring parturients received epidural analgesia. This unacceptably low number necessitated a dedicated epidural service that was subsequently initiated in June 2014 by the Department of Anaesthesiology and Critical Care to improve the quality of care in labouring patients. Methods: A retrospective follow-up audit was conducted from June 2014 to December 2015 and included data on epidural rates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…[16] This increased to 5.2% after the establishment of a dedicated epidural service. [17] The reasons for the low epidural rate in our study are multifactorial and include a limited number of anaesthetists available to provide labour epidurals. During the study period, there was a single anaesthetist on call for labour epidurals from Monday to Friday during the daytime (07h00 to 16h00) only.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…[16] This increased to 5.2% after the establishment of a dedicated epidural service. [17] The reasons for the low epidural rate in our study are multifactorial and include a limited number of anaesthetists available to provide labour epidurals. During the study period, there was a single anaesthetist on call for labour epidurals from Monday to Friday during the daytime (07h00 to 16h00) only.…”
Section: Discussionmentioning
confidence: 92%
“…[16] A follow-up study in 2014, after the establishment of a dedicated epidural service at the same hospital, revealed that the epidural rate had increased to 5.2%. [17] Epidurals are considered safe, but when serious complications occur, they can be fatal or lead to permanent harm. [6] An audit by the Royal College of Anaesthetists in 2009 [18] found the incidence of permanent harm after epidural to be 0.6 per 100 000 cases (95% confidence interval 0 -3.4), and a survey in France found an incidence of serious events related to obstetric epidural to be less than 5 in 10 000.…”
mentioning
confidence: 99%
“…[1,10,[14][15][16][17] Very few public training hospitals offered labour epidural services, but the epidural rates in public hospitals in GP were similar to those in public hospitals in Western Cape Province. [19][20] This may be a result of similar limitations in service delivery in most public maternity hospitals, but further research is needed to determine this. The epidural rates were higher in public hospitals in 2015 than those reported in a study conducted by Leonard et al [21] This is most likely a result of the initiation of a 24/7 labour epidural service in 2015 at the same GP academic hospital initially evaluated by Leonard et al [21] in 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Factors limiting the provision and uptake of labour epidural services in SA have not been fully elucidated. [20] However, insufficient knowledge, poor awareness and inadequate exposure of healthcare workers to the analgesic modality during their academic training may be contributing factors to poor rates in both the public and private sector and requires further study. [18] CS rates in GP private and public hospitals in 2015 were higher than the CS rates of 10 -15% recommended by the WHO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation